RP-HPLC Method Development and Validation for Simultaneous Quantification of Ascorbic and Gallic Acids in Natural Extract-Based Granules - Vyas, Tejas; Shah, Ujashkumar; Patel, Jayvadan; Tiwari, Mrityunjay (International Journal of Pharmaceutical Investigation, 2025)
Background Ascorbic acid and gallic acid are known for immune-boosting and antioxidant properties. Objectives To develop a straightforward, sensitive, validated, and economical reverse phase liquid chromatographic technique for the simultaneous measurement of ascorbic and gallic acid in granule formulation and natural extracts (Amla and Chyavanprash). These compounds are essential for their therapeutic benefits. Materials and Methods Ascorbic and Gallic acid were separated from the complex mixture of various polyphenols present in natural extract. At 30°C, these two compounds were separated using a Thermo C18 analytical column with an isocratic program consisting of two solvents-A & B. The ratios of Solvent- A (0.3% orthophosphoric acid in HPLC grade water) and Solvent-B (80% acetonitrile in HPLC grade water) were 85:15 v/v, and the flow rate is 0.5 mL/min. using a UV-PDA detector at a single wavelength of 250 nm. Results In accordance with ICH guidelines, the developed method was validated for linearity, precision, accuracy, robustness, Limit of Detection (LOD), & Limit of Quantification (LOQ). The granule formulation has 0.261% gallic acid and 0.079% ascorbic acid. Conclusion Ascorbic acid and gallic acid in natural extracts and granule samples were successfully quantified and validated using the RP-HPLC method. The method proved it’s simple, precise, sensitive, rapid and robust.
Keywords: Amla Extract; Ascorbic acid; Chyavanprash; Gallic acid; Method development; RP-HPLC; Validation